Extracorporeal shockwave myocardial therapy is efficacious in improving symptoms in patients with refractory angina pectoris – a multicenter study. Issue 3 (May 2015) - Prasad, Megha; Wan Ahmad, Wan Azman; Sukmawan, Renan; Magsombol, Edward-Bengie L.; Cassar, Andrew; Vinshtok, Yuri; Ismail, Muhammad Dzafir; Mahmood Zuhdi, Ahmad Syadi; Locnen, Sue Ann; Jimenez, Rodney; Callleja, Homobono; Lerman, Amir
<x xml:space="preserve">Abstract</x> Objective Medically refractory angina remains a significant health concern despite major advances in revascularization techniques and emerging medical therapies. We aimed to determine the safety and efficacy of extracorporeal shockwave myocardial therapy (ESMT) in managing angina pectoris. Methods A single-arm multicenter prospective study was designed aiming to determine the safety and efficacy of ESMT. Patients of functional Canadian Cardiovascular Society class II–IV, despite stable and optimal medical management, with documented myocardial segments with reversible ischemia and/or hibernation on the basis of echocardiography/single-photon emission computerized tomography (SPECT) were enrolled from 2010 to 2012. A total of 111 patients were enrolled, 33 from Indonesia, 21 from Malaysia, and 57 from Philippines. Patients underwent nine cycles of ESMT over 9 weeks. Patients were followed up for 3–6 months after ESMT treatment. During follow-up, patients were subjected to clinical evaluation, the Seattle Angina Questionnaire, assessment of nitrate intake, the 6-min walk test, echocardiography, and SPECT. Results The mean age of the population was 62.9±10.9 years. The summed difference score on pharmacologically induced stress SPECT improved from 9.53±17.87 at baseline to 7.77±11.83 at follow-up (P=0.0086). Improvement in the total Seattle Angina Questionnaire score was seen in 83% of patients (P<0.0001). Sublingual nitroglycerin use significantly decreased (1.14±1.01 tablets per week at baseline to 0.52±0.68 tablets per week at follow-up; P=0.0215). There were no changes in left ventricular function on echocardiography (0.33±9.97, P=0.93). The Canadian Cardiovascular Society score improved in 74.1% of patients. Conclusion This multicenter prospective trial demonstrated that ESMT is both a safe and an efficacious means of managing medically refractory angina.